Aktualisasi Pengetahuan Konten Pedagogi Guru Melalui Rencana Pelaksanaan Pembelajaran - Ita Chairun Nissa (Universitas Pendidikan Mandalika (UNDIKMA), 2015)
What does it take to become a good teacher? This question if it was compared to the Act No. 14Year 2005 on Teachers and Lecturers, then what is needed is four competencies that pedagogical competence,personal competence, social competence, and professional competence. The fourth of these competencies,actually can be built from simple things related to teachers' daily tasks. One of them is the task of designing aLesson Plan. This task becomes mandatory duty for teachers before executing an instruction in the classroom.However, many teachers who do not wholeheartedly and is regarded as a liability solely educationaladministration. If we did so, many important lessons for teachers of design a Lesson Plan in developingPedagogical Content Knowledge which is the basic building block of all four professional competence ofteachers. Pedagogical Content Knowledge is knowledge of what and why the material was taught to students aswell as how to teach it. Perhaps this seems trivial and often done daily by teachers, but whether we haveactually done significantly ?. This article reveals how Pedagogical Content Knowledge can be built through theactivity of designing a Lesson Plans.